COGNITIVE ORIENTATIONS OF ELECTRONIC MANAGEMENT: EVIDENCE FROM INFORMATION TECHNOLOGY - Huda Abdulhaleem Ibrahim; Alaa A. Mustafa (Galaxy International Interdisciplinary Research Journal, 2023)
The research aims to identify the role of electronic management in improving the performance and efficiency of institutions. Electronic management is considered a wide field for business institutions to enter into a wide world in interacting and communicating outside their borders and adapting to new trends of openness. Technology, represented by the Internet communications network and the accompanying material requirements, has made it possible for it to be a fertile and spacious ground for use and interaction with the rules and transactions of electronic administration.